1989
DOI: 10.1111/j.1365-2818.1989.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic reconstruction from energy‐filtered images of thick biological sections

Abstract: SUMMARY Energy filtration makes it possible to image a ∼0.5 μm biological section at 80 kV in the electron microscope. Based on spectra taken at different tilt angles, we chose the most probable energy loss, ΔEp ± 10 eV for each tilt angle, as the imaging energy window. A complete tilt series from + 60° to −60° at 2.5° intervals was collected on the Zeiss EM902 and used in a tomographic reconstruction of transcriptionally active chromatin in the Balbiani ring of Chironomus tentans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In other cases, where discrete deposits cannot be identified, it is necessary to use dense markers such as colloidal gold particles, deposited on one side of the thick section. Such labelling was found to be very useful in studies where a high precision is needed for 3-D reconstruction (Harauz et al, 1987;Olins et al, 1989). We also tested this labelling in our case and we found it as efficient as internal spots of silver (data not shown).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In other cases, where discrete deposits cannot be identified, it is necessary to use dense markers such as colloidal gold particles, deposited on one side of the thick section. Such labelling was found to be very useful in studies where a high precision is needed for 3-D reconstruction (Harauz et al, 1987;Olins et al, 1989). We also tested this labelling in our case and we found it as efficient as internal spots of silver (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…As one of the ultimate goals of 3-D reconstruction is tomography there is a need for a very high tilt series ( -60" to + 60" or more) (Skoglund et al, 1986;Harauz et al, 1987;Hegerl, 1989;Olins et al, 1989;Peachey &Heath, 1989) with, if possible, rotation of the section within the plane of the object-holder (Turner et al, 1989). However, until now the use of large tilt-series and of stereo-pairs has some limitations due to:…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that MPL imaging will produce problems with contrast inversion as the MPL peak shifts across the plasmon peaks and into the carbon edges Olins et al, 1989). Contrast inversion is clearly a problem for unstained or very thin samples.…”
Section: Resultsmentioning
confidence: 98%
“…By imaging with an energy-selecting window centered on the most-probable loss region, as opposed to a fixed slit at the zero-loss position, signal-to-noise ratios are dramatically increased providing shorter exposure times and slit widths can be decreased, thereby reducing chromatic aberration. A demonstration of the feasibility of this technique was first presented by Olins and coworkers in 1989 using one of the first energy-filtering instruments available at 80 keV (Olins et al, 1989). A mathematical definition of MPL will be presented in Section 2.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years EELS has also found favour among chemists and biologists (Ditchfield et al, 1972;Isaacson, 1972a,b;Bell & Liang, 1976;Costa et al, 1978;Hainfield & Isaacson, 1978;Ritzko et al, 1978;Briber & Khoury, 1988;Leapman & Ornberg, 1988;Wolf & Schwinde, 1988). The Zeiss EM 902 was the first commercial transmission electron microscope (TEM) with an integrated Castaing filter by which energy-filtered images could be obtained (Olins et al, 1988;Ottensmeyer, 1988;Rattner & Bazett-Jones, 1988;Heinrich et al, 1990). In spectrum mode EELS In recent years software for PCs has become increasingly available.…”
Section: Introductionmentioning
confidence: 99%